Modeling of Deaf Facades in the Design of the Facades of Buildings with the Index to Renewable Energy Generation - Çok, Beyza (Architecture Image Studies, 2023)
The concept of sustainability that emerged and influenced architecture has created serious environmental problems. In this study, the reasons for the use of solar energy in passive systems and the importance of passive systems in sustainable buildings are discussed. Furthermore, the construction of integrated models with passive systems was evaluated using a computer program. This study consists of eight chapters. Explain the purpose, the question and the necessity of the research. Assess why and why sustainability, its methods and alternative energy sources emerged. Exposes the design parameters of sustainable buildings, urban planning, ecology, intelligence, zero energy consumption, energy saving buildings and other types. Methods for harnessing solar energy in buildings, called active and passive systems, and their related types, discusses solar energy in buildings under several headings. The use of passive solar energy in buildings, the design parameters of buildings and spaces and the precautions or steps to be considered in different situations. Integrating the house and greenhouse as a simulation study and evaluating the efficiency of the system through a computer program, presenting the changes in tables and graphs. Conclusions and recommendations for evaluation.